Model for investment decision making by applying the multi-criteria analysis method - Puška, Adis; Beganović, Admir I; Šadić, Sead (Serbian Journal of Management, 2017)
When making an investment decision the investor has got many alternative investment options available. The task of the investor is to choose one investment that will best accomplish the objectives of the investment project. In order for an investment to be possible, it is common practice to create a document that plans and especially outlines the form of the investment project. In order to choose an investment that best meets the goals of the project, it is necessary to evaluate the project. There are evaluation methods available for the investor to assess the effectiveness of an investment project. The results given by these methods are usually conflicting, thus causing difficulties for the investor’s decision-making abilities. This paper presents a model for improving the decision process in investment. The purpose of this model is to indicate the need for using methods such as the multi-criteria analysis method in order to evaluate the effectiveness of an investment. Due to the fact that the results of the evaluation methods are often different, it is necessary to take into account that there are a number of criteria that need to be acknowledged, in order to make the best investment decision. Multi-criteria analysis can be used to rank potential investment projects and enhances the decision-making process that is required to meet the goals of an investment.